Embodying Physics-Aware Avatars in Virtual Reality - Tao, Yujie; Wang, Cheng Yao; Wilson, Andrew D.; Ofek, Eyal; Gonzalez Franco, Mar (CHI '23: Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems, 2023)
Embodiment toward an avatar in virtual reality (VR) is generally stronger when there is a high degree of alignment between the user’s and self-avatar’s motion. However, one-to-one mapping between the two is not always ideal when user interacts with the virtual environment. On these occasions, the user input often leads to unnatural behavior without physical realism (e.g., objects penetrating virtual body, body unmoved by hitting stimuli). We investigate how adding physics correction to self-avatar motion impacts embodiment. Physics-aware self-avatar preserves the physical meaning of the movement but introduces discrepancies between the user’s and self-avatar’s motion, whose contingency is a determining factor for embodiment. To understand its impact, we conducted an in-lab study (n = 20) where participants interacted with obstacles on their upper bodies in VR with and without physics correction. Our results showed that, rather than compromising embodiment level, physics-responsive self-avatar improved embodiment compared to no-physics condition in both active and passive interactions.